Morphological Interference in Studying German After English - Tajigaliyeva Marina Tleubaevna (Web of Journals Publishing, 2023)
The article examines the phenomenon of lexical and morphological interference, the influence of English as a first foreign language in the context of learning German as a second foreign language. In this case, speech transfer can be both positive and negative. The present study draws on language transfer theory. Contrastive analysis between German and English is carried out at the level of morphology and syntax.
Keywords: lexical interference, morphological interference, English, German, transfer, imperative sentence, derivation.